Pilot study on visitors' segmentation at Penang National Park based on place attachment - Ibrahim, Nabila Aiza; Isa, Siti Suriawati (Forestry Department Peninsular Malaysia, 2018)
Tourism and its branches such as ecotourism are becoming one of the major income resources for many countries including Malaysia. However, the increasing number in visitation to the ecotourism destinations have resulted into a number of challenges to the management. It has been suggested that segmentation of visitors in the ecotourism destination can contribute to the understanding the nature of the visitors which later will improve the level of customer's satisfactions and destination attachment and loyalty. The concept of place attachment focuses on the bond between human place and symbolic relationship that a human formed with that place. Data relating to this topic in Malaysia is significantly sparse in the literature. The purpose of this study is to identify visitors' segmentation at Penang National Park based on their place attachment towards the park. Visitors' segmentation can assist park stakeholders to plan for a better advertising and promotional campaign about the park in the market. A pilot study on Penang National Park was undertaken to test the readibility and suitability of the questionnaires. This can help identify the best questions to be used for studies on this topic. The reliability test run on the pilot study by using Cronbach's alpha coefficient showed above 0.7, and critical items of every dimension conformed to the content, thus, the results indicated suitability and readability of the questionnaires for the real survey.